A Compensação de reserva legal em imóvel rural incluído em processo de demarcação de terra indígena - COLARES, Gabriel de Queiroz (2021)
The research performed has as problem to investigate the juridical viability of the legal reserve compensation in rural property, including in the procedure of indigenous land demarcation. The general objective of the research is to contribute to the adequate application of the legal reserve institute and specially the legal reserve compensation as an instrument of the property’s regularization in the Legal Amazon biome; analyze the phases of demarcation of the traditionally occupied indigenous lands, aiming to point out the complexity and slowness of the procedure and; analyze the juridical repercussion of the procedure of indigenous land demarcation for legal reserve compensation. The methodology involved the doctrinal and jurisprudential survey and case analysis of the request of the Legal Reserve compensation of the Indigenous Land Maró, in the state of Pará. The research concluded that as there’s no express impossibility for the compensation of legal reserve in a property in procedure of indigenous land demarcation, it has to be applied the principle of the reasonableness and the proportionality to demand the usage of the property according to the interest of the indigenous community and environmental protection.